Skills Needs of the Private Sector in Botswana - World Bank (Washington, DC, 2015)
Human development is one of the pillars of Botswana's Country Partnership Strategy with the World Bank (2009-13). The Country Partnership Strategy (CPS) is in line with Botswana's vision 2016, which, in terms of human development, envisions the transformation of Botswana to an educated and informed nation and to a prosperous, productive and innovative nation as two key cornerstones of the strategy. In line with these objectives, the World Bank with support from the Ministry of Education and Skills Development (MoESD) embarked on analytical study entitled skills for economic growth and diversification in Botswana. The work is informed by Botswana s need to diversify its economy to facilitate stronger, more sustainable economic and employment growth and, concurrently, equip its workforce with a variety of skill sets that meet employer needs. This note is divided into six parts. The following section (section two) provides a profile of surveyed firms; sections three and four present the findings of employer and employee evaluations of the types of skills needed for employment. Section five presents the results of econometric analysis of the determinants of wages and wage growth for employees. The final section proposes some concrete recommendations on how to support the development of the skills valued by the private sector in Botswana.